STRATEGIC MANAGEMENT OF PRODUCTIVE WAQF IN ISLAMIC BOARDING SCHOOLS: A PATH TOWARD FINANCIAL SUSTAINABILITY: MANAJEMEN STRATEGIS WAKAF PRODUKTIF DI PONDOK PESANTREN: JALAN MENUJU KEBERLANJUTAN FINANSIAL - Ahmad Fatkhul Mubin; M Fatchurrohman (JASIE, 2026)
Productive waqf is a vital instrument in Islamic economics with significant potential to enhance the welfare of Islamic boarding schools (pesantren) and local communities if managed strategically. This study aims to analyze the strategic management and utilization of productive waqf at Miftahul Huda Peron Islamic Boarding School in supporting the economic empowerment of students and the surrounding community toward long-term financial sustainability. This study employs a qualitative descriptive research method, with data collected through in-depth interviews, participant observation, and documentation. The findings indicate that Miftahul Huda Peron has successfully implemented strategic management by optimizing previously static waqf assets and diversifying its business portfolio into various sectors, including retail (Mifda Mart and Bin ‘Auf Store), water refilling services (Rizqua), and stationery services (ATK Mifda). Furthermore, the management integrates core Islamic economic values, such as distributive justice, the removal of injustice (nafyu dzulum), collective welfare, and strict sharia compliance. Professionalism is fostered by appointing nadzirs (waqf managers) based on business competency, many of whom are trained through Balai Latihan Kerja (BLK). The results demonstrate that this productive waqf model contributes significantly to the institution's independence, covering up to 50% of educational operational costs and providing economic opportunities for the local community. This study concludes that professional and value-based strategic management of waqf serves as a robust path toward the financial sustainability of Islamic educational institutions.